FACTORS AFFECTING THE USE OF PUBLIC TRANSPORTATION IN SEMARANG CITY - Tazaruwah, Destin Witari; Nihayah, Dyah Maya (Efficient: Indonesian Journal of Development Economics, 2019)
Economic activities require the transfer of goods and services to be effective and efficient with transportation. The number of motorized vehicles at this time is not comparable to the place of mobility, causing traffic jams. Efforts to reduce congestion are implemented in the city of Semarang through public transportation called BRT Trans Semarang. However, these efforts have not been successful because the number of motorized vehicles has increased after the BRT, which means that the public transportation in Semarang has not been able to overcome traffic jams and facilitate the people of Semarang City. Therefore, it is necessary to know the factors that influence the community in using the BRT Trans Semarang. This study aims to determine the factors that influence the decision to use the BRT Trans Semarang and its surplus. This study used a questionnaire to 100 respondents. Distribution of questionnaires with non probability sampling methods. The dependent variable of this study is the decision to use BRT Trans Semarang. While the independent variables are travel time, accessibility to bus stops, private vehicle ownership, and the presence of online transportation. Besides the willingness to pay variable to calculate the surplus. The analysis tool used is binary logistic regression.The results showed that the accessibility variables to stops, private vehicle ownership, and the presence of online transportation had an influence on decisions in the use of the BRT Trans Semarang. Consumer surplus from BRT Trans Semarang users from the tariff of Rp. 86,000. Kegiatan ekonomi berupa perpindahan barang dan jasa akan lebih efektif dan efisien dengan transportasi. Kondisi saat ini jumlah kendaraan bermotor tidak sebanding dengan tempat mobilitasnya, sehingga terjadilah kemacetan. Upaya untuk mengurangi kemacetan melalui transportasi publik berupa BRT Trans Semarang belum sesuai dengan harapan karena masih banyaknya pengguna kendaraan pribadi. Oleh karena itu penelitian ini bertujuan untuk mengetahui faktor - faktor yang mempengaruhi masyarakat dalam penggunaan BRT Trans Semarang dan surplusnya. Penelitian ini menggunakan kuesioner yang disebarkan kepada 100 responden. Penyebaran kuesioner dilakukan dengan metode non probability sampling. Variabel dependen penelitian ini adalah keputusan penggunaan BRT Trans Semarang. Sedangkan variabel independen nya adalah waktu tempuh, aksesibilitas ke halte, kepemilikan kendaraan pribadi, dan adanya transportasi online. Selain itu variabel willingness to pay untuk menghitung surplusnya. Adapun alat analisis yang digunakan adalah regresi logistik biner. Hasil penelitian menunjukkan bahwa variabel aksesibilitas ke halte, kepemilikan kendaraan pribadi, dan adanya transportasi online memiliki pengaruh terhadap keputusan dalam penggunaan BRT Trans Semarang. Surplus konsumen pengguna BRT Trans Semarang dari tarif sebesar Rp 86.000.